Effectiveness of the Eggs Make Kids Demand-Creation Campaign to Improve Household Availability of Eggs and Egg Consumption in Young Children in Nigeria. (14th June 2022) - Kase, Bezawit Eyob; Larson, Leila; Frongillo, Edward; Gonzalez, Wendy; Erhabor, Irowa; Djimeu, Eric
Abstract: Objectives: To determine the effectiveness of the "Eggs Make Kids Smart & Bright and Strong & Active" demand-creation campaign on caregivers' behavior towards eggs, caregivers' willingness-to-pay for eggs, the availability of eggs in household, and the consumption of eggs in children 6–59 months of age in Kaduna state, Nigeria. Methods: An egg demand-creation campaign in Kaduna state targeting families of children 6–59 months of age was implemented between October 2019 and December 2020. A quasi-experimental design was used to evaluate the impact of the campaign. The intervention arm received emotionally compelling radio and TV advertisement and promotional activities and advertising at point-of-purchase, schools, and health facilities about eggs; the comparison arm received no intervention. Children 6–59 months of age in both arms (intervention n = 1359; comparison n = 1485) were assessed 14 months apart before and after the implementation of the intervention. Intent-to-treat analyses with analysis of covariance method were used to assess impact of the intervention on caregivers' behavior towards eggs, caregivers' willingness-to-pay for eggs, the availability of eggs in household, and the consumption of eggs in children 6–59 months of age. Analyses were adjusted for possible confounders and perceived effects of SARS-CoV2 on household finances and food consumption. Results: There was improved prevalence of household egg acquisition in the intervention arm compared to the comparison arm (odds ratio = 1.34, p-value < 0.0001). The intervention arm showed larger improvements in caregiver self-efficacy (β = 0.242, p-value = 0.004) and intent to feed eggs (β = 0.080, p-value = 0.021) than the comparison arm. No effects were found on child egg consumption or caregivers' willingness-to-pay for eggs. Conclusions: In Nigeria, a 14-month egg demand creation campaign improved household egg acquisition and benefited caregiver self-efficacy and intent to feed eggs but did not improve child egg consumption. Further research is needed to identify how to increase child egg consumption in the context of availability of eggs in households and favorable caregiver behavior. Funding Sources: Funding for this study was provided by the Netherland's Ministry of Foreign Affairs.